Fatores determinantes no apreçamento de títulos de dívida corporativa ao longo do tempo - Paula, Caio Crepaldi de (2012)
The present work tries to explain the evolution of credit spreads from non-convertible bonds issued by Brazilian companies during the period of 2005 to 2012. For this, a number of company specific variables are used, like, corporate leverage indexes, rating and volume outstanding. Besides that, more general variables related to economic sentiment are also used. For example, equity index, interest rates, economic indexes end yields paid by Latin American companies internationally. The econometric results tend to indicate that, diversely than the works made in developed markets, variables related to interest rates don’t seem to have relevant explanatory capabilities in determining the evolution of credit spreads during 2005 to 2012. After de 2008 crisis, however, Brazilian interest rates do seem to have some explanatory power, indicating a possible evolution to a more developed market. Equity indexes and international credit spreads levels are econometrically relevant to explain Brazilian credit spreads. Besides that, there seem to be a high tendency factor in the Brazilian corporate credit market. Changes in credit spreads in one period seem to have effects in the next period, according to the econometric model used.